REGULASI EMOSI DAN FORGIVENESS PADA REMAJA KORBAN CYBERBULLYING - Nabila Malik; Dewi Retno Suminar (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: EMOTION REGULATION AND FORGIVENESS IN CYBERBULLYING ADOLESCENCE VICTIM Forgiveness is related to the ability to control oneself and negative emotions in the form of hatred and desire to take revenge on those who have hurt. Emotion regulation needs to be done to eliminate negative emotions and replace them with positive emotions. This study aims to determine the relationship between emotion regulation and forgiveness in adolescent victims of cyberbullying. Participants in this study were 201 cyberbullying victims aged 11-22 years old. The method used is a survey through a questionnaire, using the Emotion Regulation Scale and Transgression-related Interpersonal Motivations Inventory (TRIM-18). Data analysis was done through Spearman Rank correlation test. The results of the study indicates that there is a relationship between emotion regulation and forgiveness in adolescent victims of cyberbullying. Keywords: Adolescence, Emotion Regulation, Cyberbullying, Forgiveness Forgiveness berkaitan dengan kemampuan mengendalikan diri dan emosi negatif berupa kebencian maupun keinginan untuk melakukan balas dendam pada pihak yang telah menyakiti. Regulasi emosi perlu dilakukan untuk menghilangkan emosi negatif dan menggantinya dengan emosi positif. Penelitian ini bertujuan untuk mengetahui hubungan antara regulasi emosi dengan forgiveness pada remaja korban cyberbullying. Partisipan dalam penelitian ini adalah 201 remaja korban cyberbullying yang berusia 11-22 tahun. Metode yang digunakan dalam penelitian ini adalah survey melalui kuesioner, menggunakan Skala Regulasi Emosi dan Transgression-related Interpersonal Motivations Inventory (TRIM-18). Analisis data yang digunakan adalah uji korelasi Spearman Rank. Hasil penelitian menunjukkan terdapat hubungan antara regulasi emosi dengan forgiveness pada remaja korban cyberbullying. Kata Kunci: Remaja, Regulasi Emosi, Cyberbullying, Forgiveness